1979
DOI: 10.1080/17450397909428218
|View full text |Cite
|
Sign up to set email alerts
|

Untersuchungen über die Proteinverdaulichkeit und Aminosäurenresorption in verschiedenen Abschnitten des Verdauungstraktes beim Schwein

Abstract: From two fattening pigs (average live weight 63 kg) with re-entrance cannulae both in the duodenum and the ileocecal region, the intake, the excretion and the flow rates of nitrogen, 15N, lysine and 15N-lysine are measured after the oral application of 15N-lysine as supplement of a wheat-wheat gluten diet. A scheme of the lysine metabolism of pigs is drawn on the basis of the measured values. The absorption of synthetic and native lysine as well as the endogenous and exogenous lysine contents of the duodenal a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

1979
1979
1990
1990

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 6 publications
1
5
0
Order By: Relevance
“…These results are similar to those of and Holmes et al (1974) obtained with cannulated pigs. Buraczewska et al (1979) and Wunsche et al (1979) described the flow of endogenous amino acids through cannulas in the terminal ileum of pigs even an N-free diet, and their values are approximately half those in the present experiment for the whole lower third of the small intestines; similarly the flow of total endogenous N was approximately half the level of the present study, as mentioned earlier. All the results discussed previously have referred to the flow of endogenous N in the digestive tract.…”
Section: Discussionsupporting
confidence: 81%
See 4 more Smart Citations
“…These results are similar to those of and Holmes et al (1974) obtained with cannulated pigs. Buraczewska et al (1979) and Wunsche et al (1979) described the flow of endogenous amino acids through cannulas in the terminal ileum of pigs even an N-free diet, and their values are approximately half those in the present experiment for the whole lower third of the small intestines; similarly the flow of total endogenous N was approximately half the level of the present study, as mentioned earlier. All the results discussed previously have referred to the flow of endogenous N in the digestive tract.…”
Section: Discussionsupporting
confidence: 81%
“…found that endogenous N secretion in the stomach and duodenum was unaffected by the protein level in the diet. However, in more recent reports by Krawielitzki et al (1979) and Buraczewska et al (1979), the flow of endogenous N and methionine to the duodenum was greater in pigs given a diet containing wheat gluten than when the diet given was N-free. Carlson & Bayley (1970) found that estimates of endogenous N flow by regression analysis in pigs given casein and those determined directly in pigs given an N-free diet were similar, but regression analysis with soya-bean meal as the source of dietary protein underestimated endogenous N. From the present experiment, it may be concluded that endogenous N flow can be estimated by giving an almost N-free diet or by regression analysis from pigs given diets containing casein.…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations